An Analysis of Cultural Words using Nababan’s Accuracy and Gottlieb’s Subtitling Strategies in Movie Subtitle Penyalin Cahaya - Alkafi, Dzaugy (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2025)
This research aims to analyze the accuracy of cultural word translation found in the subtitles of the film Penyalin Cahaya (The Photocopier). The method used in this research is qualitative, applying Newmark's theory of cultural word translation, Nababan's accuracy quality assessment, and Henrik Gottlieb's subtitling strategies. The cultural words and subtitling strategies found will be categorized and grouped based on how well the text is transferred from the source language to the target language. The purpose of this research is to assess the accuracy of the translation of cultural words, including material culture, social culture, organization, customs, gestures, and habits.